A high performance hybrid passive base‐isolated system - Cao, Liyuan; Li, Chunxiang (Structural control and health monitoring, 2022)
Summary This paper proposes a novel high performance hybrid passive base‐isolated system integrating the base‐isolated system (BIS) with the tuned tandem mass damper inerters (TTMDI), referred to as the BIS+TTMDI. To reveal the interaction between two components and their integrated control performance, the proposed configuration is modeled by a simplified four degree‐of‐freedom model together taking the dynamic characteristics of the isolation system, TTMDI, and superstructure into inclusion. Employing the optimization criterion defined as minimization of the dimensionless variance of superstructure displacement relative to the ground and by resorting to the particle swarm optimization, the system parameters of TTMDI are tuned to get their best integrated control performance. Evaluations are in turn unfolded on the performance taking into diverse TTMDI inertial properties and different isolation layer characteristics account and robustness, to fully explore the effectiveness of reducing both the displacement and acceleration for the isolation layer and superstructure, the TTMDI's energy dissipation mechanism and capacity, evolution of stiffness and damping, stroke, and structural frequency response. Subsequently, the findings of the BIS+TTMDI in the frequency domain is further tested via the time history analyses using the real records including both near‐field with pulse and far‐field earthquakes. In two analysis domains, the integrated performance of the proposed BIS+TTMDI is compared not only to the BIS but also to the BIS+TMDI, as well as to the BIS+TTMD and BIS+TMD. Results confirm that the BIS+TTMDI is a high performance system, namely, with high control effectiveness, high robustness, highly smaller stroke, and drastically reduced damping demand.